Waiting for spring. 10 - Anashin, 1992- (Kodansha Comics, 2019)
"With Aya's leg injured, Mitsuki wants nothing more than to see him fully recovered. And to everyone's surprise, Towa wants to help! He uses his grandfather's connections to arrange a group trip to a hot spring that will help Aya heal. Aya is reluctant to go at first, but Mitsuki manages to change his mind. Can Hojo's star player really become friends with the rest of the guys...?"--Amazon.